Assessment of calcium and vitamin D content in meals served for preschool children attending to kindergartens in some Silesian cities - Marek Stroba; Jolanta Malinowska-Borowska (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. Adequate nutrition is one of the most important factors for influencing growth and development of children. Providing adequate amounts of minerals is extremely important in the developmental age, especially in periods of intensive growth. Calcium and vitamin D deficiency may have a negative impact on the health of children, both in the short and long term. Objective. The aim of this study was to evaluate the content of calcium and vitamin D in the meals of preschoolers and to compare the obtained results to Polish dietary reference values for children aged 4-6 years. Material and methods. The study was conducted in 40 randomly selected kindergartens in some Silesian cities and were concerning 1,746 children. 10-day-menus and preschool inventory reports describing the amount of food used for meal preparation were obtained from every kindergarten. 10-day-menus were analysed in terms of calcium and vitamin D content with the use of the Dieta 5 software. The obtained results were developed in Microsoft Excel 2016. Results. The analysis of 10-days menus showed significant deficiencies in both calcium and vitamin D intake in the assessed food rations. The mean calcium level was 416.0 mg while vitamin D was 1.47 μg. The content of calcium and vitamin D in the examined 10-days menus did not meet the dietary reference values. Conclusions. The necessity to modify menus in terms of increasing the consumption of the analysed nutrients was demonstrated, as well as the need to implement nutritional education for preschool staff and parents was suggested.